Historical ties and foreign direct investment: An exploratory study - Makino, Shige; Tsang, Eric W K (Journal of International Business Studies, 2011)
Recent research suggests that the distance between countries in terms of culture, institutions, geographic proximity, and economic development matters in the foreign direct investment (FDI) decisions made by firms. This study focuses on the historical ties between countries as an additional factor affecting such decisions. In particular, it examines three major historical factors that affect cross-country ties with Vietnam, namely, Chinese occupation and conflict, French colonization, and socialist ideology, and examines the ways in which these historical ties have influenced FDI. The database consists of 631 wholly owned subsidiaries and 1215 joint ventures formed in Vietnam by multinational enterprises from 35 countries and regions between 1989 and 1999. The results indicate that firms from Hong Kong, Taiwan, France, and former and current socialist countries tended to be early movers in Vietnam, whereas firms from Mainland China tended to be late movers. Using the example of Vietnam, this study clearly shows that historical ties can provide additional explanatory power regarding FDI decisions beyond the conventional distance variables.